The fragmented landscape of fundamental rights protection in Europe : the role of judicial and non-judicial actors - Violini, Lorenza; Baraggia, Antonia (Edward Elgar Publishing, 2018)
The composite nature of the EU constitutional legal framework and the presence of different fundamental rights protection actors within the European landscape presents a complex and fragmented scenario in search of a coherent structure. This discerning book provides a thorough analysis and offers a unique perspective on the future of fundamental rights protection in Europe. With engaging contributions from both scholars and practitioners, the chapters consider not only the role of judicial actors but also the increasing relevance of non-judicial bodies, including agencies, national human rights institutions, the Venice Commission and equality bodies. The contributors cover the different features and implications of judicial and non-judicial bodies at national, supranational and institutional level, paying close attention to their interaction and the ways in which each have a role to play in a comprehensive fundamental rights policy. Particular attention is paid to both the individual dimension of rights protection and the systemic dimension of rights monitoring and advisory, which have been largely overlooked in previous studies. Taking account of both theory and practice, this book will be a valuable resource to legal scholars in the fields of human rights protection, constitutional law and EU law. Members of national and supranational human rights organizations will also find this a valuable tool in discovering more about the legal foundations of their work.